Spectral analysis of radar coherent echoes and its relation to turbulence - Pokhrel, Marshal (Universitetet i Tromsø, 2012)
The measurements of polar mesosphere summer echoes has been performed since a long time by the ground based techniques with EISCAT VHF and UHF radar system and recently with MORRO. Based on these observation, my thesis is focussed on the data obtained from manda program to get data from EISCAT 3D demonstrator antenna array in Kiruna that receives from EISCAT VHF transmitter here from Tromso in the year July 2011 to analyse the Polar Mesospheric Summer Echoes(PMSE). The thesis starts with the data analysis of the PMSE observing its parameters like spectral width, doppler shift and amplitude. These parameters are built in a profile and plotted as a function of time and height. In addition, the widely accepted fact of the dependence of PMSE with turbulence is shown in the thesis which is made by showing the profiles of dissipation rate as a function of height and time. Focus is made on calculation of spectral width and its variations with height in different times. In addition , the dissipation rate has been depicted and the physics underlying beneath it has been explained.